Digital Public Relations Communication Methods in the Field of Cybersecurity An analytical study of the website of the Arab Regional Center for Cybersecurity - Saja Khudier Abas, Asst. Lecturer (lark, 2026)
This research aims to identify the most important communication methods used by digital public relations in defining and raising awareness in the field of cybersecurity, through an analytical study of the website of the Arab Regional Center for Cybersecurity. In the field of achieving this research, the researcher relied on the survey method, which is one of the most important methods of the descriptive method, as the researcher addressed the analysis of the publications of the Arab Regional Center for Cybersecurity on its official website in order to know the most important communication methods for digital public relations in the field of cybersecurity. The time and place frame was determined on the website of the Arab Regional Center for Cybersecurity, and the time period was from 1/10/2024 to 3/30/2025. The researcher used the comprehensive inventory method of the contents of the website of the Arab Regional Center for Cybersecurity, and the researcher reached several results, the most important of which are: 1- The website of the Arab Regional Cyber ​​Security Center relies heavily on a number of public relations methods to strengthen identity and improve the public image, such as the method of persuasion, the method of developing innovations and skills, and the method of entertainment and enjoyment. 2- The website relies on the traditional public relations journalistic writing style, which relies on writing news, journalistic articles, and editorials. 3- There are several methods of modern digital public relations that could have been used to increase awareness and responsibility regarding cybersecurity issues, including the method of promoting social responsibility and enhancing the image of the institution. 4- The site lacks digital advertisements, awareness videos, and digital brochures that would raise awareness and promote the issue effectively.